2012
DOI: 10.1038/ncomms1664
|View full text |Cite
|
Sign up to set email alerts
|

Broadband light management using low-Q whispering gallery modes in spherical nanoshells

Abstract: Light trapping across a wide band of frequencies is important for applications such as solar cells and photodetectors. Here, we demonstrate a new approach to light management by forming whispering-gallery resonant modes inside a spherical nanoshell structure. The geometry of the structure gives rise to a low quality-factor, facilitating the coupling of light into the resonant modes and substantial enhancement of the light path in the active material, thus dramatically improving absorption. using nanocrystallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
181
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(188 citation statements)
references
References 47 publications
(49 reference statements)
7
181
0
Order By: Relevance
“…Figure 2i gives the schematic of a spherical shell array in which the cross-sectional electric field pattern is along one of the shell rows. 45 It was found that light is confined and guided along the structure, rather than passing through the shell directly. This way, the shell geometry would form a closed path for the photon and induce resonant WGMs at certain frequencies, depending on the shell dimensions; as a result, the resonant modes here not only improve the light trapping but also allow good coupling between propagating light and resonant modes as well as broadening of the resonant absorption peak.…”
Section: −52mentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2i gives the schematic of a spherical shell array in which the cross-sectional electric field pattern is along one of the shell rows. 45 It was found that light is confined and guided along the structure, rather than passing through the shell directly. This way, the shell geometry would form a closed path for the photon and induce resonant WGMs at certain frequencies, depending on the shell dimensions; as a result, the resonant modes here not only improve the light trapping but also allow good coupling between propagating light and resonant modes as well as broadening of the resonant absorption peak.…”
Section: −52mentioning
confidence: 99%
“…58 Unlike using particles as scattering centers to increase the optical path length, specifically, a novel light management scheme by forming whispering-gallery resonant modes (WGMs) inside of the nanocrystalline silicon (nc-Si) nanoshells has just been demonstrated, in which the shell geometry enables a lowquality factor facilitating the coupling of light into resonant modes and circulating within the shell materials with a significant longer path length as compared to that of the planar counterparts. 45 WGMs refer to a type of wave traveling around a concave surface, while the low-quality factor indicates a higher rate of energy absorbed relative to the stored energy in the system. 42 All of these are important to the realization of efficient broad-band optical absorbers here.…”
Section: −52mentioning
confidence: 99%
See 1 more Smart Citation
“…3,[22][23][24] In this context, we consider here a specific configuration of RPC shells that enhances the energy exchange between their resonant WGMs with the background EM fields. The concept of energy harvesting is therefore considered here as the ability of a given structure of exchanging with and trapping EM energy from the surrounding medium.…”
Section: Energy Harvesting With Whispering Gallery Modesmentioning
confidence: 99%
“…[5][6][7][8] Over decades of thin film technology, many different physical phenomena have been considered and partial success has been reached when a certain degree of light trapping has been demonstrated. [9][10] Solar cells incorporating hexagonal arrays of nano-columns [11][12] or nano-hole [13] embossed in the active layer, nanoimprinted electrode capable of both diffracting light and collecting the photo-generated carriers, [14][15] textured electrodes in a periodic grating [16][17] or in a random configuration, [18] 1-D photonic crystals or Bragg reflectors for semi-transparent cells, [19][20][21][22][23][24] nanospheres to couple light in the whispering gallery, [25][26][27] metallic nanoparticles to increase light absorption as well as exciton dissociation, [28][29][30] nanocubes [31] or oligomers, [32][33] exhibited an improvement relative to a given reference cell. However, light trapping or confinement has never been shown to be critical to achieve record performing thin film cells.…”
Section: Introductionmentioning
confidence: 99%